Essential oils against Varroa destructor: a soft way to fight the parasitic mite of Apis mellifera. Issue 5 (19th October 2020) - Conti, Barbara; Bocchino, Rossella; Cosci, Francesca; Ascrizzi, Roberta; Flamini, Guido; Bedini, Stefano
Abstract : Essential oils (EOs) extracted from the aromatic plants Artemisia annua, Artemisia verlotiorum, Cinnamomum verum, and Citrus reticulata were investigated as repellents against the honey bees parasitic mite Varroa destructor . In laboratory tests, all EOs except C. reticulata exerted significant repellent activity against the mite after 24 h exposure. C. verum was the most effective EO against V. destructor (median effective concentration EC50 =1.30 μL L −1 ), and the least toxic against honey bees (EC50 = 13.29 μL L −1 ). Because of its high selectivity ratio ( A. mellifera LD50 / V. destructor EC50 = 10.22), C. verum EO was then tested to control varroosis in colonies in field trials. The results of open field tests confirmed the efficacy observed in the laboratory. After one week of treatment, colonies treated with the EO showed a significant reduction of V. destructor infestation (about 65% at the dose of 25.0 μL L −1 ) and no negative effects on A. mellifera . Overall, o ur experiment indicated that C. verum EO could be used to effectively control varroosis in the hive with no side effects on the bee colonies.